Cost Efficient Resource Scheduling in Cloud Computing: a Survey - J. Assudani, Purshottam; Abimann, Satheesh (International Journal of Engineering and Technology, 2018)
Resource scheduling is a tricky task in cloud environment. QoS is the main parameter from user’s perspective for Resource scheduling, while in parallel with this task, profit is very important parameter from point of view of cloud provider. The cloud service platform controls the revenue under particular market needs. The consumer get puzzled with many cloud suppliers for storing their data because various suppliers’ varying pricing scheme. In particular, recently many studies have paying attention on shaping the bond between server-side system facts and performance experience for dropping resource wastage.The main aim of cloud supplier is to provide utmost resource usage and profit, while also decreasing the energy and cost. The user wants higher throughput and less response time. Allocating proper resources with least overhead and full resource utilization is the objective of cloud. The service requests are generated by various users in cloud. Hence proper scheduling of resources is required for better performance of system and less operative cost.